Civil society - conquerors and victims? Soho in Ottakring / Vienna, Austria. Dual commitment of an art project in urban space. - Schneider, Ula (RWTH, 2013)
In the year 1999, I initiated an urban art project in the Brunnen quarter of Vienna called Soho in Ottakring. During 14 years of continuous art practice in the same quarter, a change of perception led to diverse and at times controversial discussion about the transformation of this particular area. From an artist´s view, I would therefore like to describe the dual commitment of an urban art project to the art field and the urban social sphere as well as the often problematic role of art within a process of upgrading.
Keywords: Stadterneuerung; Stadtsanierung; Stadtquartier; Problemraum; Kunst; Gentrifizierung; Benachteiligter Stadtteil; Transformation; Intervention; Kunst im öffentlichen Raum